(untitled) (Hekima Review, 2014)
Teilhard de Chardin depicted the cosmos as a process of ascent, a series of unions. From very simple beginnings, the path leads to ever greater and more complex unities, in which multiplicity is not abolished but merged into a growing synthesis, leading to the “Noosphere,” in which spirit and its understanding embrace the whole and are blended into a kind of living organism.”